COVID-19 in the Emergency Department of the Primary Healthcare Centre Banja Luka - Banjac, Nada; Ramić, Ilija; Djokić, Snježana; Pejić, Tijana; Korać, Igor; Stojisavljević, Đordje; Todorović, Nevena (Scripta Medica, 2022)
Background / Aim: COVID-19 is acute virus disease caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS–CoV-2). It was proclaimed as pandemic starting from March 2020 and is still ongoing. COVID-19 pandemic forced all segments of the society, particularly the health sector, to function in changed and aggravating circumstances and because of the transmission and new strains of the virus it resulted in the change of the number of infected people with peaks and oscillations. Aim of this study was to make analysis of the data related to COVID-19 positive/suspect patients examined in the Primary Healthcare Centre Banja Luka in the period 15 March 2020 – 15 March 2021, which refers to the incidence of the infected persons, sex and age representation, laboratory diagnostics and clinical parameters, applied therapy, as well as the number of patients sent for the hospital treatment. Methods: Data for the analysis were obtained by the retrospective analysis of the statistical data from the electronic medical record of the examined COVID-19 positive/suspect patients in the Outpatient Clinic for Acute Respiratory Infections (ARI) and in the field. Pearson’s χ2 test of contingency was used for the comparison of differences of the observed characteristics of the examined groups. Results: Personnel of the Emergency Department (ED) of the Primary Healthcare Centre Banja Luka, in the period 15 March 2020 – 15 March 2021, examined the total of 3,937 COVID-19 positive patients and patients suspect of COVID-19. Out of that number, 3,601 patients were examined in the ED – ARI and 336 patients were examined in the field. The biggest number of patients was registered in November 2020 (768). Male sex prevailed (55.50 %) and patients of 20-50 years of age were most represented. There were 3.10 % of those highly febrile patients and 2.5 % of those with low SpO2 of under 90 %. 14.90 % of patients had higher values of troponin T and 45.50 % of them had higher values of D-dimer. In the field, 69.60 % of patients had pathological changes on lungs and 33.30 % had pathological ECG report. The number of patients sent from the ARI for further diagnostic procedure or hospitalisation to the Clinic for Infectious Diseases of the University Clinical Centre of Banja Luka was 1,191 and 258 patients were sent from the field. Conclusion: For the purpose of preventing the spread of epidemics, the ED reorganised the existing space by introducing temporary clinics – containers for the patients with acute respiratory infections and febrile status, COVID-19 suspects. Clinical parameters changed depending on the new virus strains, as well as on age distribution and infection complications.